Transcatheter Resolution of a Failed Neoconfluence in Pulmonary Atresia With Discontinuous Pulmonary Arteries - Jorge Alberto Silva-Estrada, MD; Pavel Martinez-Dominguez, MD; José Luis Colín-Ortiz, MD; Alfredo Bobadilla-Aguirre, MD; Nilda Espinola-Zavaleta, MD, PhD (JACC: Case Reports, 2024)
We present a case of a full-term newborn with complex congenital heart defects, including single-ventricle physiology and discontinuous pulmonary arteries. Prompt surgical intervention was performed, which involved pulmonary neoconfluence with autologous pericardium graft and systemic-to-pulmonary shunt placement. However, postoperative complications required stenting to address pulmonary artery stenosis.